Capoeira na educação física escolar: uma possibilidade pedagógica para o 7° ano - Rodrigues, Imer da Silva (Brasil, 2025)
This study had as general objective to experience capoeira as a pedagogical possibility for the 7th grade, aiming at the valorization of Brazilian popular culture. The study was a qualitative and exploratory research, using the case study method. Data collection involved semi-structured interviews, participant observations and documentary analysis with 7th grade students. The data analysis was performed through content analysis techniques, aiming to understand the potentialities of capoeira as a tool for valorization of body culture and promotion of human values in the public school of Parintins-AM. The results obtained through the questionnaire applied reveal significant insights about the knowledge and perception of students in relation to capoeira. The analysis of the responses indicated that most participants had no substantial prior knowledge about capoeira, with many not knowing the names of movements, instruments used and associated songs. In addition, although a significant portion (100%) reported that they liked to know the capoeira, only 53.85% expressed interest in practicing it, indicating a discrepancy between appreciation of culture and willingness for effective practice. The questionnaires also showed that family influence plays an important role, since many students have relatives who practice capoeira (41%), which can facilitate engagement. These results highlight the need for a greater insertion of capoeira in the school environment, in order to promote a broader knowledge and appreciation of this rich cultural manifestation.